Digital employee experience and affective commitment: The moderating role of collectivism and digital distance in Vietnam’s digital transformation context - Minh, Nguyen Van; Thu, Pham Thi (Edelweiss Applied Science and Technology, 2025)
This study examines how Digital Employee Experience (DEX) influences Affective Commitment (AC) among employees in Vietnam’s digital transformation era. Grounded in social exchange theory, the research proposes an integrated model in which Cultural Communication Shifts (CCS) mediate the DEX–AC relationship, while Collectivism (COL) and Digital Distance (DD) serve as contextual moderators. Data were collected from 420 employees across six sectors: fintech, e-commerce, manufacturing, education, healthcare, and public administration, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that DEX positively affects AC, both directly and indirectly through CCS. A higher level of COL enhances overall AC but weakens the effect of DEX, suggesting that collectivist norms may limit the impact of individualized digital empowerment. DD shows a negative effect on AC but no significant moderating role. The study contributes theoretically by extending SET to the digital workplace and conceptualizing CCS as a socio-cultural mechanism linking technology with employee emotions. Practically, it emphasizes the need for human-centered digital design, transparent communication, and inclusive digital upskilling to strengthen employee commitment and cultural cohesion in Vietnam’s digital transformation.